Interfacing Perforated Eardrums with Graphene‐Based Membranes for Broadband Hearing Recovery (Adv. Healthcare Mater. 20/2022). Issue 20 (19th October 2022) - Li, Chunyan; Xiong, Zhiyuan; Zhou, Lei; Huang, Weiluo; He, Yushi; Li, Linpeng; Shi, Haibo; Lu, Jiayu; Wang, Jian; Li, Dan; Yin, Shankai
Abstract : Eardrum Perforation In article 2201471 by Jiayu Lu, Dan Li, Shankai Yin, and co‐workers, multilayered reduced graphene oxide membranes, offering a combination of exceptional mechanical strength, stiffness, lightweight and biocompatibility, are demonstrated to be a unique patching material to enable the closure of perforated eardrums of rats and complete restoration of broadband hearing.